Distinctive features of technical training of football players of leading European clubs - Volokhovich, A. A.; Shilko, V. G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a comparative analysis of the main aspects of the technical training of football players from leading European clubs.